2016
DOI: 10.1002/adfm.201601850
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Graphene with a Rippled Structure as a Spacer for Improving Plasmonic Coupling

Abstract: The plasmonic coupling, the enhanced electromagnetic field occurring through a uniform and small separation between metallic particles, is required for better application to localized surface plasmon resonance. Graphene has been studied as a good spacer candidate because of its precise controllability at subnanoscale. Here, the enhancement of plasmonic coupling among metallic nanoparticles (NPs) uniformly spread out on both sides of a graphene spacer is experimentally and simulatively investigated. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Leem et al reported 3D crumpled graphene–AuNPs hybrid structures for SERS applications using a mechanical self‐assembly strategy on a thermally activated polymer . Similarly, Lee et al fabricated a rippled graphene structure on a polystyrene substrate using a thermal rippling process and demonstrated the increased plasmonic coupling and higher density of the hot spots on the rippled nanostructure . Kumar et al presented a flexible SERS sensor by depositing Ag on structured polydimethylsiloxane using a Taro leaf as the template and achieved highly sensitive detection for malachite green .…”
Section: Introductionmentioning
confidence: 99%
“…Leem et al reported 3D crumpled graphene–AuNPs hybrid structures for SERS applications using a mechanical self‐assembly strategy on a thermally activated polymer . Similarly, Lee et al fabricated a rippled graphene structure on a polystyrene substrate using a thermal rippling process and demonstrated the increased plasmonic coupling and higher density of the hot spots on the rippled nanostructure . Kumar et al presented a flexible SERS sensor by depositing Ag on structured polydimethylsiloxane using a Taro leaf as the template and achieved highly sensitive detection for malachite green .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we note that the enhancement factors are more pronounced at long wavelength. The maximum electric field intensity enhancement (| E | 2 /| E 0 | 2 ) created by monolayer MoS 2 for AuMAu and AgMAu reached up to ≈10 9 , which is much larger than previously reported metal nanostructures . Furthermore, both the AuMAu and AgMAu possessed the 3D bump structure and large amount of nanogaps among the assemblies, which is beneficial for adsorption of the analytes, therefore, making the analytes more accessible to the high density of hot spots.…”
Section: Resultsmentioning
confidence: 78%
“…Under the light illumination, the LSPR would produce a highly concentrated electromagnetic field (EF) near sharp asperities and the small gaps called “hot spots,” which can enhance orders of magnitude of the light intensity . The intensity of the “hot spots” is strongly sensitive to the gap size among the plasmonic nanostructures . Many efforts have been made to search for the efficient metallic nanostructures with optimum and uniformity gap size.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been suggested for improving the photovoltaic performances of nanostructures by exploiting the plasmonic field enhancement. Among these, the vertically formed gap‐mode plasmon as in our vertically stacked electrode structure has a few advantages over the lateral plasmonic enhancement: 1) strong electric field excitation through and perpendicular to the MLG layer enhances the light absorption within the MLG, where photoexcited carriers are generated . The lateral plasmonic enhancement results in much weaker light–matter interaction only near the shallow region of the MLG layer in the vicinity of metal NPs, whereas the vertical gap‐mode plasmon occurs through the MLG spacer and covers the entire MLG with strong near‐fields (Figure b, for visual illustration).…”
Section: Resultsmentioning
confidence: 99%